Preschoolers’ views on integration of digital technologies - Ora Segal-Drori; Anat Ben Shabat (Journal of Childhood, Education & Society, 2021)
The aim of the present study was to explore preschool children’s views on the integration of digital technologies in their school. The study included 171 Israeli children aged 3 to 6 who participated in in-depth interviews regarding their views on digital technologies in their preschool. The interviews were analyzed using content analysis. Three major views regarding digital technologies in the preschool were found: The degree to which digital technologies are necessary; the goals of the use of these technologies; the setting for using the digital technologies. Fifty percent of the children, especially the younger ones, claimed that use of these technologies is not necessary in preschool. However, most of them understood the importance of using these technologies and their contribution to many fields. In relation to the setting use, they referred to time and social aspects. The findings indicate that preschool teachers need to mediate these aspects more wisely and adapt them to the children's understanding and view toward digital technologies than actually takes place when they use them with the children.